SEASONAL SPATIAL DISTRIBUTION OF MARINE DEBRIS AT THE BEKASIâKARAWANG COASTS - Ernest Depari, Jeremy
The distribution of marine debris can be influenced by rainfall, oceanographic phenomena such as ocean currents, tides, seasons, and river discharge. Additionally, human activities can also affect it. This study aims to examine the characteristics of marine debris in Indonesia, particularly along the coasts of Bekasi and Karawang, based on type, quantity, weight, and size through surveys and field measurements during three seasons: the second transitional season of 2023, the west monsoon, and the first transitional season of 2024. The surveys and field measurements were conducted using methods derived from the 2020 Marine Debris Monitoring Guidelines by the Kementerian Lingkungan Hidup dan Kehutanan (KLHK). From what has been implemented, various types of debris were found along the coasts of Bekasi and Karawang in areas such as mangrove forests, tourist areas, fish auction places (TPI), and sparsely populated regions. In each season and location, plastic debris (PL) dominated, with a percentage range of 37.69%–95.91%. The least frequently found debris types were glass and ceramic debris (GC), paper and cardboard (PC), metal debris (ME), and other materials (OT), with a percentage of occurrence in each season not exceeding 5%. The quantity, weight, and size of the debris also varied. The most debris was found at Saung Alas Bekasi Mangrove Tourism and Cilebar Karawang Mangrove Tourism. The amount of debris in these two locations exceeded 100 items each season. Macro debris was found more frequently than meso debris. The weight of meso debris in each season ranged from 0 to 89 g/m², while the weight of macro debris in each season and location ranged from 22.70 to 289.68 g/m². The amount and density of debris along each coast were generally greater during the west monsoon season of 2024 compared to the second transitional season of 2023 and the first transitional season of 2024, except at Tanjung Pakis Beach.